The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1159/000430401
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Novel Bladder Cancer Xenograft Model in Humanized Immunodeficient Mice

Abstract: Background/Aims: The aim of this study was to develop a novel model by transplanting human bladder cancer xenografts into humanized immunodeficient mice (SCID). Methods: The animals first underwent sublethal irradiation and then were subjected to simultaneous transplantation of human lymphocytes (5 × 107 cells/mouse i.p.) and human bladder cancer cells (3 × 106 cells/mouse s.c.). Results: The xenografts developed in all 12 mice that had received bladder cancer BIU-87 cells, and the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…It is well-known that CD4 + and CD8 + T lymphocytes are the primary helper and cytotoxic T cells, respectively, which can secrete cytokines and induce the death of tumor cells [31,32]. Furthermore, NK cells are an important population of lymphocytes and have pivotal roles in both innate and adaptive immunity [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that CD4 + and CD8 + T lymphocytes are the primary helper and cytotoxic T cells, respectively, which can secrete cytokines and induce the death of tumor cells [31,32]. Furthermore, NK cells are an important population of lymphocytes and have pivotal roles in both innate and adaptive immunity [33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of animal models have been developed and used in basic tumor research. Due to the technical and ethical considerations, investigations into the immunobiology of allotransplantation can only be performed using animals, which are limited when translating the results to humans (22). Progress has been made with the development of different chimeric animal models, which can serve important roles in studies associated with cancer, transplantation biology, infectious diseases, and autoimmunity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, mice were transplanted with PBMCs at a dose of 4x10 7 /mouse, which has been shown to have an increased success rate of immune reconstruction and a reduced risk of graft vs. host disease (16,20,24). Among the various transplantation methods, the present study engrafted human PBMCs into NOD/SCID mice via an intraperitoneal injection because the method is more readily manipulated (22). After 4 weeks of immunization with human PBMCs, human CD45 + T-lymphocytes were detected in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Nude mice, purchased from Beijing laboratory animal center, were exposed to 2.5 Gy X-ray at a dose rate of 1.2 Gy/min (RS2000Pro, Rad Source Technologies, USA) [ 42 44 ]. On withdrawal of X-ray exposure after 2 days, the mice were randomly divided into three groups, LY-10 cells (1×10 7 cells per animal were injected subcutaneously into the right abdomen of mice from all four groups).…”
Section: Methodsmentioning
confidence: 99%